Assessment of the national drug education program implementation in region XII, Philippines - Tidalgo, Hermer; Regalado, Precy (Goodwood Publishing, 2025)
Purpose: This study assessed the level of implementation of the National Drug Education Program (NDEP) and the extent of stakeholder engagement in the Barkada Kontra Droga (BKD) initiatives in Region XII. It also examined the relationship between these two components to support the development of continuity programs in school-based drug prevention. Methodology/approach: A descriptive-correlational design was employed using a validated, researcher-made questionnaire administered to 388 school heads and NDEP coordinators across eight divisions in Region XII. Data were analyzed using mean, standard deviation, and Spearman’s rank correlation. Results/findings: The NDEP was highly implemented across curriculum and instruction, co-curricular activities, teacher and staff involvement, parent education, and research evaluation. Stakeholder engagement in BKD was also reported to a great extent, particularly in implementation and campaign initiatives. A strong positive correlation (r = 0.68, p = 0.000) was found between NDEP implementation and stakeholder engagement. Conclutions: Greater NDEP implementation appears to support stronger stakeholder involvement in BKD initiatives. School-community collaboration remains central to sustaining preventive education. Limitations: The study was limited to school heads and NDEP coordinators and relied on self-reported data from a single time point. Future studies should include broader stakeholders and track long-term outcomes. Contribution: The study affirms the importance of strengthening implementation strategies to encourage broader participation in drug prevention efforts across schools and communities.